Tailored rigidity of W/O Pickering emulsions using diacylglycerol-based surface-active solid lipid nanoparticles. Issue 23 (26th October 2021) - Li, Guoyan; Lee, Wan Jun; Tan, Chin Ping; Lai, Oi Ming; Wang, Yong; Qiu, Chaoying
Abstract : W/O Pickering emulsion with tailored rigidity was obtained by using medium- and long chain DAG (MLCD) based solid lipid nanoparticles (SLNs) with or without the aid of other surfactants. Abstract : Pickering water-in-oil (W/O) emulsions were fabricated by using medium-long chain diacylglycerol (MLCD)-based solid lipid nanoparticles (SLNs) and the connection between the characteristics of the SLNs and the colloidal stability of the emulsions was established. Via melt-emulsification and ultrasonication, MLCD-based SLNs with particle sizes of 120–300 nm were obtained with or without other surfactants. The particle size of the SLNs was influenced by the chemical properties of the surfactants, and surfactants decreased the contact angle of SLNs at the oil–water interface. Gelation was observed in SLNs modified by sodium stearoyl lactylate and lecithin, whereas the addition of Tween 20 resulted in a homogeneous SLN solution. The adsorption of surfactants onto SLN surfaces caused the production of higher amounts of α crystals accompanied by delayed crystallization onset which contributed to the reduction of particle size, interfacial tension and oil wetting ability. The W/O emulsions with higher rigidity and physical stability can be obtained by varying surfactant types and by increasing SLN mass ratios to 60%, whereby more SLNs are adsorbed at the droplet surface as a Pickering stabilizer. This study provides useful insights for the development of diacylglycerol-based SLNs and Pickering W/O emulsions which have great potential for food, cosmetic and pharmaceutical applications.